Language Impairments in Individuals With Coffin-Siris Syndrome - Vasko, Ashley; Schrier Vergano, Samantha A. (Frontiers in Neuroscience, 2022)
1 Coffin-Siris Syndrome (CSS, MIM 135900) is a now well-described, multiple congenital anomaly/intellectual disability syndrome classically characterized by fifth digit/nail hypoplasia, coarse facial features, and a range of organ-system related anomalies. Since its initial description in 1970, and the discovery of associated genes in 2011, CSS now encompasses a wide range of phenotypes and abilities caused by pathogenic variants in the BAF complex (often referred to as ‘BAFopathy’). It appears that this gene complex leads to speech and language impairments in this population, and subsequently we have reviewed individuals in the CSS/BAF registry to understand the prevalence and degree of this particular learning difference. We have examined the frequency of delayed language acquisition, augmented communication device use, and speech intervention therapies. While the majority of children with pathogenic variants in the BAF complex have language-related struggles, the exact mechanism is not yet fully understood. At the time of writing, there are 284 individuals in the CSS/BAF registry with known variants in the following genes; ARID1B (n=174), SMARCA4 (n=41), ARID1A (n=20), SMARCB1 (n=20), ARID2 (n=14), SOX11 (n=10), and SMARCE1 (n=5). While speech delays in individuals with CSS are expected, a full analysis of these delays has yet to be detailed. In the CSS/BAF registry, we identified 183 (64%) individuals with language-related challenges and 90 (32%) individuals that are non-verbal.